2010
DOI: 10.1002/ccd.22527
|View full text |Cite
|
Sign up to set email alerts
|

Radial versus femoral access for orally anticoagulated patients

Abstract: The radial access is as efficacious and safe as the femoral route for coronary angiography in fully anticoagulated patients, but is likely to result in fewer access-site complications in patients who also undergo PCI.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
28
0
1

Year Published

2010
2010
2018
2018

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 56 publications
(32 citation statements)
references
References 71 publications
3
28
0
1
Order By: Relevance
“…1 Deviations from normal anatomy are not infrequent, occurring in 18.5% of 386 cadavers studied by McCormack et al 2 Unilateral abnormalities were more common than bilateral (24.5% and 6.3%, respectively). Similar findings have also been reported by Fujii et al and Ziakas et al 3,4 Rodriguez-Baeza et al have proposed 4 groups of anomalies: isolated persistence of the median artery; high origin of the ulnar artery; high origin of the radial artery, and duplication of the brachial artery, either with or without anastomosis at the cubital fossa. 5 The most common anomaly is a high origin of the radial artery, either from the brachial or axillary artery, and has been shown in 14.27% of cadaveric samples and 9.75% in angiographic examinations.…”
Section: Discussionsupporting
confidence: 85%
“…1 Deviations from normal anatomy are not infrequent, occurring in 18.5% of 386 cadavers studied by McCormack et al 2 Unilateral abnormalities were more common than bilateral (24.5% and 6.3%, respectively). Similar findings have also been reported by Fujii et al and Ziakas et al 3,4 Rodriguez-Baeza et al have proposed 4 groups of anomalies: isolated persistence of the median artery; high origin of the ulnar artery; high origin of the radial artery, and duplication of the brachial artery, either with or without anastomosis at the cubital fossa. 5 The most common anomaly is a high origin of the radial artery, either from the brachial or axillary artery, and has been shown in 14.27% of cadaveric samples and 9.75% in angiographic examinations.…”
Section: Discussionsupporting
confidence: 85%
“…These thresholds are rather arbitrary and based on scant data. Of note, a new study of fully anticoagulated patients undergoing PCI from either the radial or femoral access site suggests a major advantage to the use of radial access regarding periprocedural bleeding (187). Overuse of parenteral vitamin K may make it difficult to re-establish an antithrombin effect following the procedure, therefore allowing the patient's INR to drift downward after stopping the medication is preferred.…”
Section: Patients Receiving Antiplatelet and Antithrombin Agentsmentioning
confidence: 97%
“…On the other hand, a femoral approach with vascular closure device (Angioseal) was noninferior to a radial approach in reducing postcardiac procedure complications 17. However, studies have shown that patients with uninterrupted warfarin undergoing radial approach had less vascular complications 18,19…”
Section: Discussionmentioning
confidence: 99%